2020
DOI: 10.1101/2020.02.10.941336
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring protected-area outcomes with leech iDNA: large-scale quantification of vertebrate biodiversity in Ailaoshan nature reserve

Abstract: 29Environmental DNA (eDNA) has great potential to complement visual surveys, camera 30 trapping, and bioacoustics in measuring biodiversity. We report here a large-scale attempt 31 to use DNA from leech-ingested bloodmeals to estimate vertebrate occupancy at the scale 32 of an entire protected area: the 677 km 2 Ailaoshan national-level nature reserve in Yunnan 33 province, southwest China. We contracted 163 park rangers to collect leeches in 172 pa-34 trol areas, resulting in 30,468 total leeches, divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 113 publications
(220 reference statements)
0
12
0
Order By: Relevance
“…-Long-term monitoring will be necessary for tracking the biodiversity consequences of conversion from simple to heterogeneous forests and for comparing different anthropogenic treatments. Studies in China, the UK, and Borneo have shown that DNA metabarcoding is an efficient and standardizable tool for measuring how animal biodiversity in forests varies as a function of management and inherent condition (Barsoum et al, 2019;Edwards et al, 2014;Hua et al, 2016;Ji et al, 2013Ji et al, , 2020Wang et al, 2019;Yang et al, 2014;Yang et al, 2016;Zhang et al, 2016). We also think that there is considerable scope for using remotely sensed measures (multispectral and LiDAR) to efficiently generate environmental covariates for the large-scale mapping and monitoring of pest outbreaks like bark beetles in particular (Ji et al, 2007; and terrestrial biodiversity in general (Bush et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…-Long-term monitoring will be necessary for tracking the biodiversity consequences of conversion from simple to heterogeneous forests and for comparing different anthropogenic treatments. Studies in China, the UK, and Borneo have shown that DNA metabarcoding is an efficient and standardizable tool for measuring how animal biodiversity in forests varies as a function of management and inherent condition (Barsoum et al, 2019;Edwards et al, 2014;Hua et al, 2016;Ji et al, 2013Ji et al, , 2020Wang et al, 2019;Yang et al, 2014;Yang et al, 2016;Zhang et al, 2016). We also think that there is considerable scope for using remotely sensed measures (multispectral and LiDAR) to efficiently generate environmental covariates for the large-scale mapping and monitoring of pest outbreaks like bark beetles in particular (Ji et al, 2007; and terrestrial biodiversity in general (Bush et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In terrestrial ecosystems, eDNA and iDNA have primarily been used to detect species of interest (Lopes et al, 2020;Schnell et al, 2012Schnell et al, , 2015 or to assess general patterns of biodiversity and ecosystems (Calvignac-Spencer et al, 2013;Deiner et al, 2017;Ji et al, 2020;Schnell et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To access iDNA in terrestrial ecosystems, two predominant "invertebrate systems" have emerged in recent years: the use of carrion fly-derived DNA (Calvignac-Spencer et al, 2013; Kocher et al, 2017;Rodgers et al, 2017;Schubert et al, 2015) and the use of host DNA derived from hematophagous leeches (Abrams et al, 2019;Ji et al, 2020;Schnell et al, 2015Schnell et al, , 2018Tilker et al, 2020a;Weiskopf et al, 2018). While leechderived DNA has in the past been used to understand the composition of mammalian communities in tropical rainforests (Ji et al, 2020;Tessler et al, 2018;Weiskopf et al, 2018), the approach has not, to the best of our knowledge, been used to assess species genetic diversity.…”
Section: Introductionmentioning
confidence: 99%
“…The emerging molecular field of iDNA has contributed to the knowledge on leech diet and leech-derived iDNA is now used as a complementary tool to traditional vertebrate monitoring methods (Schnell et al, 2012;Ji et al, 2020). Such leechderived iDNA studies have focused almost exclusively on terrestrial bloodfeeding leeches, and in line with the geographical distribution of (Borda et al, 2008), they have been used to detect vertebrates in Asia (Vietnam, Laos, Malaysia, Japan), Africa (Madagascar) and Oceania (Australia and Tasmania) (Abrams et al, 2019;Drinkwater et al, 2018;Fahmy et al, 2019;Ji et al, 2020;Morishima et al, 2020;Nguyen et al, 2021;Schnell et al, 2018;Schnell et al, 2012;Tilker et al, 2020. As these haemadipsid leeches have an Indo-Pacific distribution, if iDNA from leeches is to be used for vertebrate monitoring elsewhere in the world, the vertebrate dietary range of non-haemadipsid leeches will need to be assessed, i.e.…”
Section: Introductionmentioning
confidence: 99%